Lingkungan Bermain terhadap Perkembangan Sosial Emosional pada Anak Usia Prasekolah di PAUD Barunawati Surabaya - Heru Sulistijono; Bambang Heriyanto; Hermin Tumini (JURNAL PENELITIAN KESEHATAN, 2017)
Playing is the most important element for the development of children's physical, emotional, mental, intellectual, creative and social. The research objective investigate the influence of social environment on the development of emotional play in preschoolers in early childhood.This study design analytic correlations, by the time a cross-sectional design. Independent variables play environmental research, study the dependent variable social-emotional development of pre-school age children. ECD student population of 82 children. Large sample 68 based on the inclusion criteria and exclusively with the selection of the sample using simple random sampling. The instrument uses a check list playing environment and social emotional development.Results presented in the form of cross-tabulation and narrative and statistical test Multiple Logistic Regression obtained significant level ρ = 0,000Environmental research results play a good kid that amounted to 35 children (51.5%), just 31 children (45.6%), and less than 2 children (2.9%). Social development of the child's emotional well a majority of the 35 children (51.5%), just 26 children (38.2%) and less than 7 children (10.3%).There are environmental influences play on emotional social development in preschoolers. Hopefully, the teachers always pay attention and develop methods of learning and play for children, so that children do not get bored in play. Because playing for children is learningKeywords: Playing Environment, Social Emotional Development, Childhood